2020
DOI: 10.1002/esp.4872
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological evolution and sediment stratigraphy of numerically simulated alluvial fans

Abstract: When a sediment laden river reaches a flat basin area the coarse fraction of their sediment load is deposited in a cone shaped structure called an alluvial fan. In this article we used the State Space Soil Production and Assessment Model (SSSPAM) coupled landform–soilscape evolution model to simulate the development of alluvial fans in two‐ and three‐dimensional landforms. In SSSPAM the physical processes of erosion and armouring, soil weathering and sediment deposition were modelled using state‐space matrices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 45 publications
0
10
0
2
Order By: Relevance
“…• Lateral variability of these characteristics is greatest at the transition between the proximal and medial zone. et al, 2003;Welivitiya et al, 2020), single-channel belts (Karssenberg & Bridge, 2008) and parts of sedimentary basin fills (Bridge & Leeder, 1979;Yan et al, 2017). We suggest that linking governing parameters (initial surface, hydrology and sediment characteristics) to the resulting topology of architectural elements leads to a predictive stratigraphic model of DFS.…”
Section: Highlightsmentioning
confidence: 94%
“…• Lateral variability of these characteristics is greatest at the transition between the proximal and medial zone. et al, 2003;Welivitiya et al, 2020), single-channel belts (Karssenberg & Bridge, 2008) and parts of sedimentary basin fills (Bridge & Leeder, 1979;Yan et al, 2017). We suggest that linking governing parameters (initial surface, hydrology and sediment characteristics) to the resulting topology of architectural elements leads to a predictive stratigraphic model of DFS.…”
Section: Highlightsmentioning
confidence: 94%
“…Its strength is in incorporating pedogenesis processes such as weathering and armouring into the landform evolution framework and is capable of simulating the soil profile evolution on an evolving landform. In previous work the performance of SSSPAM has been demonstrated through simulation of a synthetic hillslope (Welivitiya et al, 2019) and a synthetic alluvial fan (Welivitiya et al, 2020). This demonstrated that SSSPAM is capable of simulating various aspects of landform evolution observed in the field.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…Hairsine & Rose, 1992a, 1992b, with the major focus being on erosion. Modelling deposition is a research area that needs to be addressed, given its importance both for landscape evolution and gully evolution (Barnhart et al, 2020a;Coulthard & Skinner, 2016;Welivitiya et al, 2016Welivitiya et al, , 2019Welivitiya et al, , 2020.…”
Section: Model Features and Functionalitymentioning
confidence: 99%